Approximation of Classes of Analytic Functions by de la Vallée-Poussin Sums - Rukasov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For upper bounds of the deviations of de la Vallée-Poussin sums taken over classes of functions that admit analytic extensions to a fixed strip of the complex plane, we obtain asymptotic equalities. In certain cases, these equalities give a solution of the corresponding Kolmogorov–Nikol’skii problem.